'Amid: Islamic Integrative Approach as Survey Model - Marliyah; Yafiz, Muhammad; Dharma, Budi; Syarbaini, Ahmad Muhaisin B. (UIN Raden Mas Said Surakarta, 2022)
Research and development require tools to approach and obtain an overview of the system, these tools include interviews, questionnaires, surveys, observations, and others. QS An-Nahl Verse 43 is a popular verse that is widely used to represent appropriate to ask, this terminology is closely related to what is known as a sample. However, in contrast to the sample, the meaning intended by the verse is beyond the scope of the sample, in this study, it is termed as 'Amid. In market research, such as research on how well educational products are produced by universities, the number of response rates affects the conclusions that are built, so the sampling approach does not correlate well. The research uses 'Amid, as an approach model that is able to increase the response rate and at the same time the best reference in questioning the assessment of higher education products that are the object of research. The study found that the 'Amid' model has more quality data than the commonly used survey approach with a better travel time. The next research is suggested to try the implementation of the 'Amid' model in market research for other products.